The concept of non-conviction-based asset forfeiture as a special coercive measure in eradicating criminal acts of corruption - Tolib Effendi; Mifta Hurrahman Maulana; Ananda Chrisna Dewy Panjaitan (Komisi Pemberantasan Korupsi, 2025)
The efforts to eradicate corruption in Indonesia have yet to demonstrate substantial outcomes at the implementation level. Indeed, the law's provisions for the eradication of corruption are commendable, with the imposition of capital punishment for those found guilty of corruption being a notable aspect. However, this legislative initiative appears to be merely a rhetorical exercise in legal romanticism for the community, without the requisite accompanying enforcement mechanisms to ensure its implementation. The aim of this study is to provide a reconstruction of the understanding of law enforcement in the context of corruption interpretation. Additionally, this study seeks to ascertain the congruence between the legal principles and the actual practices of law enforcement. The present study employs a normative legal methodology, utilizing secondary data that is subjected to qualitative analysis. The findings of this study indicate the presence of a dichotomy between the legal framework and the practices of law enforcement, suggesting that the efforts undertaken to combat corruption may not have been as effective as desired. Judges have demonstrated a tendency to interpret corruption in a narrow manner, frequently imposing lenient sentences on corrupt individuals. Consequently, the prevalence of corruption is not declining; instead, it is escalating in all domains of social and state life. This issue demands meticulous consideration, as the ramifications of corruption are pervasive and deleterious to all parties. To address this pressing issue, law enforcement officials must demonstrate the fortitude to implement the provisions of the law effectively. Anticipated outcomes include the establishment of an anti-corruption legal culture in Indonesia, with the initial phase being the alignment between the legal substance and the actions of law enforcement officials.